Core Lithofacies Analysis of Reservoir Interval (Albian—Cenomanian) Bentiu Formation of SE Muglad Basin, Sudan - Ahmed Ali Hassan Taha, Abdel Hadi Abd Rahman, Wan Yusoff Wan Ism, . (2017)
This study presents the analysis of lithofacies of the subsurface reservoir horizon of Bentiu Formation (Late Albian—Cenomanian) from the SE Muglad basin in Sudan. A detailed core description to analyze and study the different lithofacies, facies association, and architectural elements and to infer the depositional environment is conducted.